2016
DOI: 10.1080/23744235.2016.1183816
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic algorithm for tuberculous pleurisy using the ELISPOT assay on peripheral blood and pleural effusion

Abstract: A diagnostic algorithm combining ELISPOT assays and ADA levels in pleural fluid appears to be a promising and non-invasive approach for patients with suspected TB pleurisy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…As a common extrapulmonary TB, Tuberculous pleurisy (TBP) accounts for 25% of TB cases in China (2)(3)(4). The diagnosis of TBP is difficult (5,6), with the thoracoscopic pleural pathology as the gold standard method (7). However, thoracoscopic pleural biopsy is an invasive operation with the issues of considerable risks and cost.…”
Section: Introductionmentioning
confidence: 99%
“…As a common extrapulmonary TB, Tuberculous pleurisy (TBP) accounts for 25% of TB cases in China (2)(3)(4). The diagnosis of TBP is difficult (5,6), with the thoracoscopic pleural pathology as the gold standard method (7). However, thoracoscopic pleural biopsy is an invasive operation with the issues of considerable risks and cost.…”
Section: Introductionmentioning
confidence: 99%
“…After loss of special phenotypical T-cell surface markers, these cell populations are probably unable to re-enter the bloodstream and become enriched at the site of disease [9,10]. In contrast to detection of M. tuberculosis-specific effector T-cells in peripheral blood, detection of M. tuberculosis-specific effector T-cells by the interferon (IFN)-γ release assay at the site of the infection has a high diagnostic accuracy for active TB even when AFB and M. tuberculosis DNA are not detectable from local samples such as bronchoalveolar lavage (BAL) [11][12][13][14][15], pleural fluid [16,17], pericardial fluid [18], cerebrospinal fluid [19] or ascites [20]. ELISPOT test results are available within 24 h.…”
Section: Introductionmentioning
confidence: 99%
“…After mycobacterium tuberculosis infection, macrophages in lesion site will be activated and IFN-γ content in pleural effusion and blood will gradually increase ( 20 ). Studies have shown that IL-27 has a dual regulatory effect on Th1-type immune responses in tuberculous diseases ( 21 , 22 ). On one hand, IL-27 can induce the differentiation of CD4 + in to Th1.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular immune function plays an important role in the development of immune diseases. Related studies showed that mycobacterium tuberculosis control was closely related with macrophage ( 4 , 5 ). T cells spot test (T-Spot TB) was reported to possess relatively high sensitivity in the detection of extrapulmonary tuberculosis ( 6 ).…”
Section: Introductionmentioning
confidence: 99%